2021
DOI: 10.51791/njap.v32i2.1044
|View full text |Cite
|
Sign up to set email alerts
|

Performance and carcass characteristics of broiler chicken fed high fibre sunflower seed cake diets

Abstract: A feeding trial was conducted to assess the level of inclusion of high fibre sunflower seed cake (HFSSC) protein as ror soyabean cake protein replacement  for soybean cake protein in the diets of broiler chicken at 0,25,50,75, and 100%. At the starter phase feed intake and feed efficiency ratio were significantly (p,0.05) increased as the level of HFSSC increased in the diets . weight gain and protein efficiency ratio were however significantly (p,0.05) reduced when over 25% of HFSSC was included in the diets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Birds fed with 80 ppb level ppb level also had the highest gizzard weight. This could be attributed to the amount of work required of the musclar wall of the organ to comminute the feed particles (Johnson and McNab, 1983;Adeniji, 2005). Fasuyi (2007) also reported that gizzard are known to naturally increase in size to accommodate the introduction of bulkiness in diets.…”
Section: Discussionmentioning
confidence: 99%
“…Birds fed with 80 ppb level ppb level also had the highest gizzard weight. This could be attributed to the amount of work required of the musclar wall of the organ to comminute the feed particles (Johnson and McNab, 1983;Adeniji, 2005). Fasuyi (2007) also reported that gizzard are known to naturally increase in size to accommodate the introduction of bulkiness in diets.…”
Section: Discussionmentioning
confidence: 99%